Economic Situation of the Tourist Accommodation Capacity on North-west and Center of Romania - Duma, Daniela Aurelia; Blaga, Radu (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
In the present paper we continue the research work that we intended it over the years on regional tourism in recent years, the evolution of certain regions and understanding economic phenomena and disparities between regions. As such, they work in computing capacity and activity status of tourist accommodation in the North West and Centre regions known to me (the author) who also develop in terms of tourism quite similar. We used comparative methods to analyze statistical data taken from the Statistical Yearbook of Romania, the study stretching over a period of several years, and last but not least, analysis of land proposed in the two study regions (North-West and Central region).